Pendidikan Kristen sebagai Fondasi Teologis dan Historis dalam Konteks Modern (Jurnal Ilmu Pendidikan Keagamaan Kristen : Arastamar, 2025)
Christian education rests on the principle that all learning should be God-centred and directed to glorify Him. In the context of today's pluralistic society and digital age, Christian education faces major challenges such as globalisation, moral degradation and secularisation. This article offers theological and historical reflections on education in the life of the church, tracing its roots in the Bible and church history from the time of the apostles to the Protestant Reformation. Christian education not only transfers knowledge, but also shapes learners' character and faith through a holistic approach that involves spiritual, intellectual and social aspects. Through a qualitative-descriptive method with an integrative approach between educational theology and church historiography, this article emphasises the importance of contextual, missionary and discipleship-based Christian education. By living the educational heritage of the church, Christian education today is called to be light and salt in the midst of a culture of materialism and relativism. The curriculum of Christian education needs to be transformed by making Christ the centre, and building transformative relationships between teachers and students. Thus, Christian education is able to answer the challenges of modern times without losing the identity and integrity of faith.